Physiological responses of Plantago algarbiensis and P. almogravensis shoots and plantlets to low pH and aluminum stress - Martins, Neusa (2013)
We investigated the impact of low pH and aluminum (Al) stress on the growth, nutrients concentration, chlorophyll a fluorescence, photosynthetic pigment contents, proline and carbohydrate accumulation in shoots and plantlets (leaves and roots) of Plantago almogravensis and P. algarbiensis. Both species accumulated considerable and similar amounts of Al in their tissues, mainly in the roots. The presence of Al caused a significant reduction on root elongation in P. algarbiensis. Low pH and Al induced significant changes on nutrient accumulation, but no significant alterations on the maximum efficiency of PSII (Fv/Fm), quantum yield of PSII photochemistry (FiPSII), quantum yield of regulated energy dissipation (FiNPQ) and quantum yield of non-regulated energy dissipation (FiNO) were detected in both species in response to these stresses. However, Al increased significantly the nonphotochemical quenching and the hlorophyll b content and decreased the PSII excitation pressure (1 - qp) in P. almogravensis leaves. Both stress treatments induced carbohydrate accumulation in the shoots and roots of this species, but not in leaves. In P. algarbiensis, low pH and Al decreased the photosynthetic pigment contents in the shoots, whereas Al stimulated the carbohydrate accumulation in the leaves. Although our data showed that both species are tolerant to Al3+ and H+, P. almogravensis appeared to be more adapted to maintain cellular physiology and growth under those conditions.